Preparation and Release Profiles in Vitro/Vivo of Galantamine Pamoate Loaded Poly (Lactideco-Glycolide) (PLGA) Microspheres - Du, Liping; Liu, Shankui; Hao, Guizhou; Zhang, Li; Zhou, Miaomiao; Bao, Yueqing; Ding, Bing; Sun, Qinyong; Zhang, Guimin (Frontiers in Pharmacology, 2021)
Patient’s poor compliance and the high risk of toxic effects limit the clinical use of galantamine hydrobromide. To overcome these drawbacks, the sustained-release microspheres of galantamine pamoate were successfully developed using an oil/water emulsion solvent evaporation method in this study. Physicochemical properties of galantamine pamoate microspheres were carefully characterized, and the in vitro and in vivo drug release behaviors were well studied. Results showed that the morphology of optimized microspheres were spherical with smooth surfaces and core-shell interior structure. Mean particle size, drug loading and entrapment efficiency were 75.23±1.79 μm, 28.01±0.81% and 87.12±2.71%, respectively. The developed microspheres of galantamine pamoate were found to have a sustained release for about 24 days in vitro and the plasma drug concentration remained stable for 17 days in rats. These results indicated that galantamine-loaded microspheres could achieve the sustained drug release purpose and be used in clinical trial.